Kebijakan Pemerintah Daerah tentang Wajib Belajar Madrasah Diniyah Awaliyah di Kabupaten Pandeglang - Rosyadi, A. Rahmat; Mujahidin, Endin; Muchtar, Affandi (Ta’dibuna: Jurnal Pendidikan Islam, 2013)
The implementation of MDA in Pandeglang has received recognition (legitimacy) of the Local Government formally Pandeglang in the form of legislation (regulations). The purpose of this policy to improve student achievement in the field of Islamic religious education as evidenced by the Madrasah Education Graduate Certificate Diniyah Awaliyah (STTB-MDA) as a requirement for continuing education to higher education. Compulsory education policy background to solve problems and MDA obstacles in the implementation of MDA associated with an educational component, namely: (1) residents learn, (2) educators, (3) curriculum, (4) Facility, (5) finance, (6) teaching and learning, and (7) Management. The case study uses a qualitative descriptive approach, which focused on policy and policy implementation using MDA compulsory primary and secondary data sources. The research concluded that the policy of compulsory education has reached the goals of MDA with the following indicators: Regulation of MDA compulsory education policy as a juridical foundation consists of Local Regulations, Rules and Regulations Regent Education Office and the Ministry of Religious Affairs Office Pandeglang; The finishing MDA problems toward positive changes associated with educational components, namely: community learning, educators, curriculum, infrastructure, finance, teaching and learning activities, and management; MDA policy objectives of compulsory education as a condition of continuing to higher education already begun, although the effectiveness enforcement begin 2012; Compulsory education policy implementation goes according to MDA goals and targets of policy stakeholders, MDA education providers, communities and citizens to learn; Significant policy impact in improving student achievement in the field of Islamic religious education. Based on the results of the study recommended that local government policy on Compulsory Education Pandeglang MDA can be applied in other areas in the administration of MDA is more conducive. Keyword: Diniyah Awaliyah, policy, madrasah, local government, compulsory education